Boy21 - Quick, Matthew 1973- (Little, Brown and Company, 2012)
Finley, an unnaturally quiet boy who is the only white player on his high school's varsity basketball team, lives in a dismal Pennsylvania town that is ruled by the Irish mob, and when his coach asks him to mentor a troubled African American student who has transferred there from an elite private school in California, he finds that they have a lot in common in spite of their apparent differences.
Keywords: Schwarze. USA; Emotional problems of teenagers -- Fiction; Irish Americans -- Juvenile fiction; Gangsters -- Juvenile fiction; High schools -- Juvenile fiction; Violence -- Juvenile fiction; Basketball stories; Friendship -- Juvenile fiction; African Americans -- Juvenile fiction; Emotional problems -- Fiction; Irish Americans -- Fiction; Gangsters -- Fiction; High schools -- Fiction; Violence -- Fiction; Basketball -- Fiction; Friendship -- Fiction; African Americans -- Fiction; Pennsylvania -- Juvenile fiction; Pennsylvania -- Fiction; Jugendbuch